Pengaruh Persepsi Risiko, Manfaat, Dan Kemudahan Penggunaan Terhadap Minat Belanja Online Melalui Kepercayaan Dan Sikap Pada Konsumen Zalora Di Surabaya - Karnadjaja, Claudia Cindy; Tulipa, Diyah; Lukito, Robertus Sigit Haribowo (Kajian Ilmiah Mahasiswa Manajemen, 2017)
The purpose of this research is to study the influence from perceived risk, perceived usefulness, and perceived ease of use toward trust and attitude, and the impact of trust and attitude toward online shopping intention. The sample in this research was taken to 150 respondents who have purchased online and know e-commerce Zalora. The data were collected using questionnaire method and the analysis technique in this research use structural equation model (SEM). The result of this research shows that perceived ease of use has positive impact toward perceived usefulness and both of them have positive impact toward attitude. The other result of this research shows that perceived risk has negative effect toward trust and attitude. The result also shows that trust and attitude have positive impact toward online shopping intention.